Bad Humor Race and Religious Essentialism in Early Modern England. - Coles, Kimberly Anne (University of Pennsylvania Press, 2022)
Race, in the early modern period, is a concept at the crossroads of a set of overlapping concerns of lineage, religion, and nation. Bad Humor charts how these concerns converged around a pseudoscientific system that confirmed the absolute difference between Protestants and Catholics and justified English colonial domination.